Deutschland, Russland, Komintern. II. Dokumente (1918-1943). Nach der Archivrevolution: Neuerschlossene Quellen zu der Geschichte der KPD und den deutsch-russischen Beziehungen - Albert, Gleb (Archive des Kommunismus - Pfade des XX. Jahrhunderts, 2014)
Since its creation in 1998, the "German-Russian Historical Commission" has conducted research on the Communist International. Thanks to the archival revolution, the Commission has succeeded in closing important gaps in earlier research on German-Russian relations and the history of German communism. This volume contains over 500 documents, and will become a standard work long consulted by future researchers.